Factors Influencing Corporate Payout Policy: A Survey of Malaysian Public Listed Companies - Yakubova, Roza (2007)
The study addresses two research questions: 1) Out of a given set of factors, which one influnece corporate payout policy in Malaysia companies? 2) Do views of managers differ between different types of companies? The primary research objective of this dissertation is to identify wether a set of given factors, which identified and adopted from the relevent literature, influences corporate payout policy in Malaysian public listed companies and wether the views of manager regarding factors determining payout pilcy differ between managers of different types of companies-multinational and domestic companies. Additionally, the study aims to find out managers of public listed companies in Malaysia regard stable payout policy as an important consideration.